Management and Quality of Services in Pristinaâ€™s Hotelier Industry - Petrit Hasanaj; BekÃ« Kuqi; Besmir Ahmetaj (Prizren Social Science Journal, 2018)
Management of tourism hotel industry and especially the quality of services in hotel industry are important and successful factors of business.